A Pan-Cancer Analysis of the Oncogenic and Immunogenic Role of m6Am Methyltransferase PCIF1 - Jin, Ming-Zhu; Zhang, Yi-Gan; Jin, Wei-Lin; Wang, Xi-Peng (Frontiers in Oncology, 2021)
Background: PCIF1 is identified as the only-known methyltransferase of N6,2′-O-dimethyladenosine (m6Am) in mRNA. However, its oncogenic and immunological role in cancer research are at an initial stage. Methods: Herein, we carried out a pan-cancer analysis of PCIF1, with a series of datasets (e.g. TIMER2.0, GEPIA2, cBioPortal). Results: PCIF1 expression was higher in most cancer than normal tissues and was discrepant across pathological stages. Highly expressed PCIF1 was positively correlated with overall survival (OS) or disease-free survival (DFS) of some tumors. PCIF1 expression had a positive correlation with CD4+ T cells infiltration in kidney renal clear cell carcinoma (KIRC), CD8+ T cells, macrophages and B cells in thyroid carcinoma (THCA) and immune checkpoint genes (ICGs) in LIHC; but a negative correlation with CD4+ T cells, neutrophils, myeloid dendritic cells and ICGs in THCA. It also affected tumor mutational burden (TMB) and microsatellite instability (MSI) of most tumors. Conclusion: PCIF1 expression was correlated cancer prognosis and immune infiltration, suggesting it to be a potential target for cancer therapy.